Incorporating Limestone Powder and Ground Granulated Blast Furnace Slag in Ultra-high Performance Concrete to Enhance Sustainability - Yashovardhan Sharma; Meghana Yeluri; Srinivas Allena; Josiah Owusu-Danquah (International Journal of Concrete Structures and Materials)
Abstract While ultra-high performance concrete (UHPC) offers numerous advantages, it also presents specific challenges, primarily due to its high cost and excessive cement content, which can pose sustainability concerns. To address this challenge, this study aims to develop cost-effective and sustainable UHPC mixtures by incorporating ground granulated blast furnace slag (GGBFS) and limestone powder (LP) as partial replacements for portland cement. Eight fiber-reinforced UHPC mixtures were investigated, with a water-to-cementitious materials (w/cm) ratio of 0.15. In four of the UHPC mixtures, 25% of the cement was replaced with GGBFS, and further, LP was added as a mineral filler, partially substituting up to 20% of the cement. In the remaining four mixtures, cement was replaced with only LP up to 20% (without GGBFS). The 28-day compressive strength of the UHPC mixture with 25% GGBFS and 20% LP was 149 MPa, 3.50% lower than the mixture without GGBFS. Its 28-day flexural strength decreased by 30%. Increasing LP replacement reduced drying and autogenous shrinkage, with a 29% shrinkage reduction at 20% LP replacement. Moreover, UHPC mixtures with GGBFS exhibited lower shrinkage compared to those without GGBFS for all LP replacements up to 20%. For evaluating the sustainability of UHPC mixtures, the cement composition index (CCI) and clinker to cement ratio (CCR) were determined. For 20% LP replacement with 25% GGBFS, CCI was 3.6 and the CCR was 0.5, 38% decrease from the global clinker to cement ratio. Overall, 20% LP replacement UHPC mixtures with and without GGBFS can produce UHPC class performance and reduce the environmental impact.